Cycle-supermagic labeling for some families of graphs
A simple graph G = (V(G), E(G)) admits a cycle-covering if every edge in E belongs to at least one subgraph of G isomorphic to a given cycle C. The graph G is C-magic if there exists a total labeling f: V(G) ∩ E(G) -; 1,2,..., |V(G)| + |E(G)| such that for every subgraph H' = (V(H'),E(H')) of G isomorphic to C, the sum σ v(H') f(v) + ) f(e)is instant. When (f(v)) : v ϵ V(G)